PENGARUH LITERASI PERPAJAKAN DAN AKSESIBILITAS INFORMASI PAJAK DIGITAL TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI : (STUDI KASUS KPP PRATAMA BEKASI UTARA TAHUN 2024) - Meylita, Akhwati; Zahran, Wahidin Septa (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Tax revenue is the main source of state income. However, the level of compliance among individual taxpayers remains a challenge, particularly in the submission of the annual tax return (SPT). At KPP Pratama Bekasi Utara, data over the last five years shows that the submission ratio of SPT compared to the number of taxpayers required to file has experienced fluctuations and has not yet reached the expected target. Meanwhile, digitalization efforts by the Directorate General of Taxes through services such as DJP Online and e-Filing have not been fully utilized by all individual taxpayers. This study aims to determine the influence of tax literacy and the accessibility of digital tax information on individual taxpayer compliance. The research uses a quantitative approach with data collected via a Google Form questionnaire. The sample consisted of 100 respondents selected using a simple random sampling technique. Data were analyzed using simple and multiple linear regression with the help of SPSS. The results show that tax literacy has a significant influence on taxpayer compliance with a contribution of 15.1%, while digital tax information accessibility also has a significant influence of 11.9%. Simultaneously, both variables affect individual taxpayer compliance by 18.4%, while the remaining percentage is influenced by other factors outside this study.